INFLUENCE OF LASER BEAM PROFILE ON LIGHT SCATTERING BY HUMAN SKIN DURING PHOTOMETRY BY ELLIPSOIDAL REFLECTORS - M. A. Bezuglyi; N. V. Bezuglaya; S. Kostuk (Приборы и методы измерений, 2018)
The correct accounting of laser emitter parameters for improvement of diagnostic authenticity of methods of optical biomedical diagnostic is important problem for applied biophotonic tasks. The purpose of the current research is estimation of influence of energy distribution profile in transversal section of laser beam on light scattering by human skin layers at photometry by ellipsoidal reflectors.Biomedical photometer with ellipsoidal reflectors for investigation of biological tissue specimens in transmitted and reflected light uses laser probing radiation with infinitely thin, Gauss-type and uniform cross-section profile. Distribution of beams with denoted profiles, which consist of 20 million photons with wavelength 632.8 nm, was modeled by using of Monte-Carlo simulation in human skin layers (corneous layer, epidermis, derma and adipose tissue) of various anatomic thickness and with ellipsoidal reflectors with focal parameter equal to 16.875 mm and eccentricity of 0.66.The modeling results represent that illuminance distribution in zones of photometric imaging is significantly influenced by the laser beam cross-section profile for various thickness of corneous layer and epidermis in transmitted and reflected light, and also derma in reflected light. Illuminance distribution for adipose tissue in reflected and transmitted light, and also derma in transmitted light, practically do not depend of laser beam profile for anatomic thicknesses, which are appropriate for human skin on various sections of body.There are represented results of modified Monte-Carlo simulation method for biomedical photometer with ellipsoidal reflectors during biometry of human skin layers. For highly scattered corneous layer and epidermis the illumination of middle and external rings of photometric images changes depending from the laser beam profile for more than 50 % in transmitted and 30 % in reflected light. For weakly scattering skin layers (derma and adipose layer) the influence of profile can be observed only for derma in reflected layer and is equal not more than 15 %.